More immigrants, less death: an analysis of immigration effects on county-level drug overdose deaths, 2000-2015 - Feldmeyer, Ben (Criminology, 2022)
Public and political discourse has routinely suggested that immigration is linked to higher community levels of violence and drug problems. In contrast to these claims, research has consistently shown that immigration is not associated with greater violence at the macro level. However, few studies have examined the links between immigration flows and community drug problems. The current study seeks to address this gap in research by providing a county-level longitudinal analysis of immigration and drug overdose deaths both overall and by substance type for the 2000 to 2015 period and provides an analysis of homicide for comparison with prior immigration-crime research. In addition, this analysis compares immigration-overdose relationships across immigrant destination types. The current project relies on overdose and homicide data drawn from the Centers for Disease Control's Restricted Access Multiple Cause of Death Mortality files combined with data on county social, economic, health, and legal contexts drawn from multiple macro-level data sources. Findings reveal that immigration is not associated with higher levels of overdose or homicide deaths, and when effects are significant, immigration is linked to lower levels of overdose mortality across multiple substances and destination types.